Obtenção e estudo de polímeros supramoleculares derivados de ácidos carboxílicos-meglumina em fase aquosa - Cassimiro, Douglas Lopes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Supramolecular polymers are monomer units held together by intermolecular interactions. The reversible nature of the interactions makes that supramolecular polymer be under thermodynamic conditions with the monomers. Thus the polymer chains undergo reversible breaking and reformation making the supramolecular material highly susceptible to temperature, solvents, pH, mechanical force, radiation and so on. Only a few compounds are able to undergoing supramolecular polymerization, once to obtain high polymerization degrees in bulk or in solution is required a strong and directional intermolecular force. When any type of organic acid is reacted with meglumine occurs the formation of a ionic pair, called carboxilate-meglumine compound. This study shows the amphiphilic carboxilate-meglumine compounds originated from fatty acids, suffer polymerization in aqueous phase by hydrophobic interaction and hydrogen bonds. The monomers adopt a lamellar array that result in a supramolecular polymer which form a tridimensional net where the water is immobilized forming a hydrogel. The relationship between polymerization and the carbonic chain of fatty acid allowed identify that the hydrophilic/hidrophobic is the property that controls the supramolecular polymerization of the carboxilate-meglumine compound in water. To prove that were used the estearic acids (octadecanoic) and oleic acid (9-cis-octadecanoic) that have chains of C18 size; and the saturated acids with distinct chains as underdecanoic (C11) and hexadecanoic (C16). The dynamic behavior of these materials was evaluated, once the intermolecular interactions of supramolecular polymer present a reversible character that is dependent of temperature and concentration. Finally, we studied the potential of stearate-meglumine hydrogel associated with antifungals (ketoconazole and fluconazole), as a strategy for inhibiting biofilm of Candida albicans, the fungus...

Polímeros que possuem monômeros unidos via interações intermoleculares são definidos como polímeros supramoleculares. A natureza reversível das interações assegura que o polímero supramolecular exista em equlíbrio termodinâmico com seus monômeros. Isto implica que as cadeias do polímero podem romper-se e recombinar, tornando este material hábil em responder a mudanças externas ao sistema, como variação de temperatura, solvente, variação de pH, força mecânica, radiação, etc. Poucas substâncias são capazes de sofrer polimerização supramolecular, pois para que propriedades poliméricas sejam aparentes em fase sólida ou em solução, as interações intermoleculares devem ser fortes e direcionais. Reagindo qualquer tipo de ácido orgânico com um aminocarboidrato denominado meglumina é produzido o par iônico, genericamente chamado de carboxilato-meglumina. Este estudo mostra que compostos carboxilato-meglumina anfifílicos derivados de ácidos graxos polimerizam em fase aquosa via interações hidrofóbicas e ligações de hidrogênio. Os monômeros adotam um arranjo lamelar e o polímero supramolecular resultante, se estrutura em uma rede tridimensional de fibras onde a água é imobilizada formando um hidrogel. A correlação entre a polimerização e a característica da cadeia carbônica proveniente do ácido graxo precursor foi elucidada, permitindo identificar que o balanço hidrofílico/hidrofóbico é a propriedade que governa a polimerização supramolecular dos compostos carboxilato-meglumina em água. Para tanto foram utilizados ácidos análogos com cadeias de tamanhos iguais C18, neste caso, os ácidos esteárico (octadecanóico) e oleico (9-cis-octadecenóico) e também ácidos saturados de cadeias distintas, undecanóico (C11) e palmítico (hexadecanóico) (C16). O caráter reversível das interações intermoleculares no polímero supramolecular em função da...
Keywords: Química supramolecular; Polimeros; Ligação de hidrogenio; Equilibrio; Acidos graxos; Balance